Species- and strain-specific microbial modulation of interferon, innate immunity, and epithelial barrier in 2D air–liquid interface respiratory epithelial cultures - Mian Horvath; Ruoyu Yang; Diana Cadena Castaneda; Megan Callender; Elizabeth S. Aiken; Anita Y. Voigt; Ryan Caldwell; José Fachi; Blanda Di Luccia; Zoe Scholar; Peter Yu; Andrew Salner; et al. (BMC Biology)
Abstract Background The microbiome regulates the respiratory epithelium’s immunomodulatory functions. To explore how the microbiome’s biodiversity affects microbe-epithelial interactions, we screened 58 phylogenetically diverse microbes for their transcriptomic effect on human primary bronchial air–liquid interface (ALI) cell cultures. Results We found distinct species- and strain-level differences in host innate immunity and epithelial barrier response. Strikingly, we found that host interferon, an antiviral response, was one of the most variable host processes. This variability was not driven by microbial phylogenetic diversity, bioburden, nor by the microbe’s ability to stimulate other innate immunity pathways. Conclusions Microbial colonization differentially stimulates host gene expression with variations observed across phylogenetically diverse microbes and across different strains of the same species. Our study provides a foundation for understanding how the respiratory microbiome’s biodiversity affects epithelial, and particularly antiviral, innate immunity.